Effects of Extracorporeal Shock Wave Therapy on Numerical Rating Scale of Pain in Patients with Chronic Plantar Fasciitis. Issue 3 (2nd October 2015) - Kordi Yoosefinejad, Amin; Ghalamghash, Reza
Abstract: Objectives: Heel pain secondary to plantar fasciitis [PF] is a common problem making up 11–15% of foot problems. Extracorporeal shock wave therapy [ESWT] is a relatively new approach that has evolved as a treatment option, but there are controversies about the applied parameters. The effects of ESWT have not been studied in an Iranian population, so the aim of our study was to investigate the effects of ESWT on patients with PF. Methods: A total of 168 patients [70 men and 98 women] with the mean age of 50 ± 4.55 years were treated between March 2010 and 2013. Each patient was treated four times [once a week] and received a total of 8000 pulses. The parameters were set according to patients' perception of pain and increased gradually in accordance with patients' tolerance. Results: We evaluated the visual analog scale [VAS] of pain, TUG test, and activities of daily living [ADLs] in patients during the first session and immediately after the completion of the sessions. We also followed up the patients for a mean of 10.5 months. Both VAS and ADLs have demonstrated improvement immediately after the completion of treatment course and during the follow up period. TUG test showed significant statistical differences among the evaluations. Conclusions: ESWT is a safe and efficient treatment method for recalcitrant plantar fasciitis, especially, if prescribed dosage would be considered individually.